Electromagnetic Actuation and Sensing in Medical Robotics - Ren, Hongliang; Sun, Jinji; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book highlights electromagnetic actuation (EMA) and sensing systems for a broad range of applications including targeted drug delivery, drug-release-rate control, catheterization, intravitreal needleless injections, wireless magnetic capsule endoscopy, and micromanipulations. It also reviews the state-of-the-art magnetic actuation and sensing technologies with remotely controlled targets used in biomedicine.
Introduction about the role of EMA/EMS in medicine -- Magnetic Actuated Microparticles with their applications -- Magnetic Actuated Catheterization Robotics (Mesle scale) -- Magnetic Actuated Needle-less injectors -- Magnetically suspended manipulators -- Magnetic sensing in surgical robotics -- MRI guided procedures -- Conclusions and future perspectives.
Keywords: Biomedical engineering; Control engineering; Robotics; Automation; Artificial intelligence; Medicine -- Research; Biology -- Research; Endoscopic surgery; Biotechnology; Biomedical Engineering and Bioengineering; Control, Robotics, Automation; Artificial Intelligence; Biomedical Research; Minimally Invasive Surgery; Biotechnology